Experiences of People With Dementia in Pakistan: Help-Seeking, Understanding, Stigma, and Religion. (17th November 2018) - Willis, Rosalind; Zaidi, Asghar; Balouch, Sara; Farina, Nicolas
Abstract: Background and Objectives: The prevalence of dementia will increase in low- and middle-income countries like Pakistan. Specialist dementia services are rare in Pakistan. Public awareness of dementia is low, and norms about family care can lead to stigma. Religion plays a role in caregiving, but the interaction between dementia and Islam is less clear. Research Design and Methods: Qualitative interviews were carried out with 20 people with dementia in Karachi and Lahore. Interviews were conducted in Urdu, translated to English, and respondents' views on help-seeking experiences, understanding of diagnosis, stigma, and religion were analyzed thematically. Results: Although some people with dementia understood what dementia is, others did not. This finding shows a more positive perspective on diagnosis in Pakistan than previously thought. Help-seeking was facilitated by social and financial capital, and clinical practice. Stigma was more common within the family than in the community. Dementia symptoms had a serious impact on religious obligations such as daily prayers. Participants were unaware that dementia exempts them from certain religious obligations. Discussion and Implications: Understanding of dementia was incomplete despite all participants having a formal diagnosis. Pathways to help-seeking need to be more widely accessible. Clarification is needed about exemption from religious obligations due to cognitive impairment, and policy makers would benefit from engaging with community and religious leaders on this topic. The study is novel in identifying the interaction between dementia symptoms and Islamic obligatory daily prayers, and how this causes distress among people living with dementia and family caregivers.